Nonlinear association between the serum uric acid-to-creatinine ratio and all cause mortality in patients with hypertension: a ten-year cohort study using the NHANES database - Yiming Zeng; Yingying Chen; Jie Li; Liang Chen (Scientific Reports)
Abstract The serum uric acid-to-creatinine ratio (UCR) may be a simple method for assessing xanthine oxidase overactivation, which may contribute to an increase in serum uric acid production and oxidative stress. In this study, we investigated the nonlinear association between the UCR and long-term mortality in patients with hypertension. Data were acquired from the National Health and Nutrition Examination Survey database, and a total of 11,346 patients with hypertension were included. We explored the nonlinear link between the UCR and all-cause mortality via spline smoothing, threshold saturation, and log-likelihood ratio tests. The results were validated through a competing risk model. A nonlinear pattern emerged between the UCR and all-cause mortality in hypertensive patients, with an inflection point at 4.3. Below this point, an increased UCR was associated with a decreased mortality risk (OR = 0.80, 95% CI: 0.68–0.94, P = 0.008), whereas above this point, the risk increased (OR = 1.21, 95% CI: 1.07–1.36, P = 0.004). The competing risk model yielded similar findings for cardiovascular and chronic kidney disease-related deaths. In patients with hypertension, the UCR nonlinearly predicted all-cause mortality, with a notable inflection at 4.3. These findings suggest that the UCR is a valuable prognostic indicator for assessing long-term outcomes in patients with hypertension.